Periventricular leukomalacia in a preterm neonate with early onset Capnocytophaga sepsis - Vora, Shrenik; Panjangam, Pandian; Rajadurai, Victor Samuel (Indian Journal of Case Reports, 2016)
Capnocytophaga sputigena is a slow-growing, capnophilic, gram negative, anaerobic, fusiform bacilli residing in oropharyngeal cavity of mammals. In humans, it causes localized periodontal infections and sporadic invasive infections in immunocompromised persons. Infrequently, it does cause chorioamnionitis and perinatal infections and is generally of lower morbidity risk in fetus and neonates. We describe a rare case report of early-onset neonatal Capnocytophaga sepsis with culture negative meningitis in preterm infant who developed early cystic periventricular leukomalacia in second week of life. Though neonatal Capnocytophaga infection is probably under-reported due to its fastidious nature and subclinical infection in mother, this case reminds that Capnocytophaga may be responsible for some occult cases of early neonatal septicemia, and that the organism may be more virulent in premature neonates with possibility of development of periventricular leukomalacia and neurological morbidities.